The south-central zoning of Brazil for corn crops - Cordeiro, Celta Maria Torres; Silva, João Gilberto Corra da (Pesquisa Agropecuaria Brasileira, 2014)
A critical appraisal of the present zoning of the Center-South Region of Brazil for the corn crop is made, based on the cultivar by location interaction. Results of the National Corn Experiment in the years 1974/1975, 1975/1976 and 1976/1977 were used. Locations were clustered according to the similarity of their interaction pattern by a clustering method known as "average linkage unweighted". The results showed the presence of two nuclei that can be identified with the actual Center and South regions, and suggested the possibility of some improvement of the present zoning. However, a new regionalization is not proposed due to the inadequacy of the data for thatpurpose and the complexity of the problem.